Brock biology of microorganisms - Madigan, Michael T., 1949-; Brock, Thomas D. (Boston : Pearson, 2012)
This introductory microbiology text balances current science coverage with the concepts essential for understanding the field of microbiology. Updated with findings from new research, and a new design, the 12th edition speaks to today's students while maintaining the depth and precision science majors need
I. PRINCIPLES OF MICROBIOLOGY 1. Microorganisms and Microbiology 2. A Brief Journey to the Microbial World 3. Cell Structure and Function in Bacteria and Archaea II. METABOLISM AND GROWTH 4. Nutrition, Culture, and Metabolism of Microorganisms 5. Microbial Growth III. MOLECULAR BIOLOGY AND GENE EXPRESSION 6. Molecular Biology of Bacteria 7. Archael and Eukaryotic Molecular Biology 8. Regulation of Gene Expression IV. VIROLOGY, GENETICS, AND GENOMICS 9. Viruses and Virology 10. Genetics of Bacteria and Arachaea 11. Genetic Engineering 12. Microbial Genomics V. METABOLIC DIVERSITY AND COMMERICAL BIOCATALYSES 13. Phototrophy, Chemolithotrophy, and Major Biosyntheses 14. Catabolism of Organic Compounds 15. Commercial Products and Biotechnology VI. MICROBIAL EVOLUTION AND DIVERSITY 16. Microbial Evolution and Systematics 17.Bacteria: The Proteobacteria 18. Other Bacteria 19. Archaea 20. Eukaryotic Cell Biology and Eukaryotic Microorganisms 21. Viral Diversity VII. Microbial Ecology 22. Methods in Microbial Ecology 23. Major Microbial Habitats and Diversity 24. Nutrient Cycles, Biodegradation, and Bioremediation 25. Microbial Symbioses VIII. ANTIMICROBIAL AGENTS AND PATHOGENICITY 26. Microbial Growth Control 27. Microbial Interactions with Humans IX. IMMUNOLOGY 28. Immunity and Host Defense 29. Immune Mechanisms 30. Molecular Immunology X. DIAGNOSING AND TRACKING MICROBIAL DISEASES 31. Diagnostic Microbiology and Immunology 32. Epidemiology XI. HUMAN- AND ANIMAL-TRANSMITTED INFECTIOUS DISEASES 33. Person-to-Person Microbial Diseases 34. Vectorborne and Soilborne Microbial Pathogens XII. COMMON SOURCE INFECTIOUS DISEASE 35. Wastewater Treatment, Water Purification, and Waterborne Microbial Diseases 36. Food Preservation and Foodborne Microbial Diseases Appendices 1 and 2 Glossary Index
Previous edition: 2009.
Includes bibliographical references and index.
Keywords: Microbiology